Metaphorical Representation of the European Union in Political Cartoons in English and Latvian - Liepa, Solveiga; Šaudiņa, Vilma; Oļehnovičs, Dmitrijs (Research in Language, 2021)
The study is carried out in the framework of Conceptual Metaphor Theory, but since it considers political cartoons that, apart from linguistic, involve also other modes, the findings of theoreticians researching visual and multimodal metaphors are applied. The purpose of the present study is to identify and analyse the visual and multimodal metaphors encountered in cartoons focusing on the European Union matters and to find out if political events are presented in cartoons in English and Latvian on the basis of the same conceptual metaphors.